Demethylation of histone H3K36 and H3K9 by Rph1: a vestige of an H3K9 methylation system in Saccharomyces cerevisiae? - Klose, R; Gardner, K; Liang, G; Erdjument-Bromage, H; Tempst, P; Zhang, Y (2007)
Histone methylation is an important posttranslational modification that contributes to chromatin-based processes including transcriptional regulation, DNA repair, and epigenetic inheritance. In the budding yeast Saccharomyces cerevisiae, histone lysine methylation occurs on histone H3 lysines 4, 36, and 79, and its deposition is coupled mainly to transcription. Until recently, histone methylation was considered to be irreversible, but the identification of histone demethylase enzymes has revealed that this modification can be dynamically regulated. In budding yeast, there are five proteins that contain the JmjC domain, a signature motif found in a large family of histone demethylases spanning many organisms. One JmjC-domain-containing protein in budding yeast, Jhd1, has recently been identified as being a histone demethylase that targets H3K36 modified in the di- and monomethyl state. Here, we identify a second JmjC-domain-containing histone demethylase, Rph1, which can specifically demethylate H3K36 tri- and dimethyl modification states. Surprisingly, Rph1 can remove H3K9 methylation, a histone modification not found in budding yeast chromatin. The capacity of Rph1 to demethylate H3K9 provides the first indication that S. cerevisiae may have once encoded an H3K9 methylation system and suggests that Rph1 is a functional vestige of this modification system.